Hispanic-American Independence in Martí's thought - González-Zúñiga, Carlos Rodolfo (2021)
José Martí's interpretation of the Hispanic American independence processes is analyzed in this article. The first part mentions Martí's criticism of colonial elements that survive in the new republics; the autonomous character of the independence process, and the proposal of a second independence. Following  the analysis, the concept of natural man is used to understand the role of the popular indigenous and mestizo social sectors as revolutionary subjects in the framework of Guatemala's independence struggle against Spanish colonialism in the work Patria y Libertad [Homeland and Freedom].  Likewise, a critique of the liberal context of the play Patria y Libertad is analyzed and two considerations on theater that incorporate the value of territoriality in theatricality are presented. Finally, it is concluded that the play Patria y Libertad expresses the role of interculturality and the leading role of popular social sectors in the development of the second independence.